Mycoplasma synoviae haemagglutination involves immunodominant surface membrane proteins undergoing phase- size- and antigenic-variation - Dušan BENČINA; Mojca NARAT (Acta Agriculturae Slovenica)
In the majority of Mycoplasma synoviae (MS) strains their VLHA haemagglutinins cleave into N-terminal and C-terminal parts. In MS strain ULB 925 (clone KF9) it was found that monoclonal antibodies (mAbs) 3E10, 5G6 and 4G2 recognise the C-terminal parts of its haemagglutinin, designated pMSA, as integral membrane proteins of 51 and 53 kDa. In the same MS clone mAb 125 recognized the N- terminal parts, designated pMSB, as integral membrane proteins of 47 and 49 kDa. However, in MS strain K1723 mAbs 3E10, 5G6 and 125 reacted with an uncleaved VLHA haemagglutinin of about 90 kDa. In MS strain ULB 925 clones their haemagglutinin- positive (HA+) and haemadsorption- positive (HAD+) phenotypes synthesised pMSA defined by mAbs. About 1 % of the populations which ceased to produce pMSA and produced truncated pMSB1 forms (of 27 to 30 kDa) lost the HA+ and HAD+ phenotype. The switching of the synthesis of pMSA proteins was heritable and usually reversible. In strain ULB 925 (clone KF9) certain populations which ceased to produce pMSA defined by mAb 3E10 started to produce pMSB antigenic variant, recognised by another mAb. In MS strains, besides antigenic- variation of pMSA and pMSB, their size- variants were also observed and they were recognised by antibodies of chickens infected with MS.